Future Technology Photonics – Is the Product Development Ready for Automotive?: How to comply with automotive requirements for the product development process to enter and survive the market. Issue 4 (1st August 2019) - Bey, Nadine
Abstract: Photonic technologies will be an essential part of future automobiles. But to become an automotive supplier and successfully persist in that industry, companies will have to fulfill very formal requirements regarding their product development process: Automotive SPICE. This article shortly summarizes its essentials and the greatest differences between the photonics and automotive world. Then it guides the reader through the most important quick wins to make the product development of companies in the relevant photonics field ready for Automotive SPICE.